America First Bilateral Health Agreements Threaten to Undermine the Multilateral Global Health Order - Sharifah Sekalala; Shajoe J. Lake; Allan Maleche; Maria Birungi; Frank Ssekamwa (Journal of Law, Medicine & Ethics, 2026)
Abstract During the second Trump administration, the United States has signed bilateral health agreements with at least 27 states across Africa and Latin America, reshaping how signatory countries finance, regulate, and monitor their health systems. Grounded in the America First Global Health Strategy, these agreements are being signed as US withdrawal from WHO restructures global health. This column explores how this turn to bilateralism risks weakening multilateral legal obligations on capacity development, access and benefit sharing, transparency, and the right to health.